Alcohol Misuse and Co‐Occurring Mental Disorders Among New Soldiers in the U.S. Army. (24th November 2016) - Stein, Murray B.; Campbell‐Sills, Laura; Gelernter, Joel; He, Feng; Heeringa, Steven G.; Nock, Matthew K.; Sampson, Nancy A.; Sun, Xiaoying; Jain, Sonia; Kessler, Ronald C.; Ursano, Robert J.; ,
Abstract : Background: Problem drinking that predates enlistment into military service may contribute to the overall burden of alcohol misuse in the Armed Forces; however, evidence bearing on this issue is limited. This study examines prevalence and correlates of alcohol misuse among new U.S. Army soldiers. Methods: Cross‐sectional survey data were collected from soldiers reporting for basic combat training. The survey retrospectively assessed lifetime alcohol consumption and substance abuse/dependence, enabling estimation of the prevalence of lifetime binge drinking and heavy drinking in a sample of 30, 583 soldiers and of probable alcohol use disorder (AUD) among 26, 754 soldiers with no/minimal lifetime use of other drugs. Co‐occurrence of mental disorders and other adverse outcomes with binge drinking, heavy drinking, and AUD was examined. Discrete‐time survival analysis, with person‐year the unit of analysis and a logistic link function, was used to estimate associations of AUD with subsequent onset of mental disorders and vice versa. Results: Weighted prevalence of lifetime binge drinking was 27.2% (SE = 0.4) among males and 18.9% (SE = 0.7) among females; respective estimates for heavy drinking were 13.9% (SE = 0.3) and 9.4% (SE = 0.4). Among soldiers with no/minimal drug use, 9.5% (SE = 0.2) of males and 7.2% (SE = 0.5) of females had lifetime AUD. Relative to no alcohol misuse, binge drinking, heavy drinking, and AUD were associated with increased odds of all mental disorders and other adverse outcomes under consideration (adjusted odds ratios [AORs] = 1.5 to 4.6; p s < 0.001). Prior mental disorders and suicidal ideation were associated with onset of AUD (AORs = 2.3 to 2.8; p s   < 0.001), and prior AUD was associated with onset of mental disorders and suicidal ideation (AORs = 2.0 to 3.2, p s < 0.005). Conclusions: Strong bidirectional associations between alcohol misuse and mental disorders were observed in a cohort of soldiers beginning Army service. Conjoint recognition of alcohol misuse and mental disorders upon enlistment may provide opportunities for risk mitigation early in a soldier's career. Abstract : Weighted prevalence of lifetime post‐traumatic stress disorder, suicidal behavior, major depressive disorder, and panic disorder by categories of alcohol misuse among new soldiers in a sample of the US Army, assessed during basic training. Standard errors range from 0.1 to 1.5%. All four co‐occurring conditions were more prevalent among soldiers with lifetime binge drinking, lifetime heavy drinking, lifetime probable alcohol use disorder (AUD) and past‐year probable AUD than among soldiers with no lifetime alcohol misuse (all p 's < 0.001).